Observation of tropical positive cloud-to-ground flashes accompanied by chaotic and regular pulse trains - Mohammad Sabri M.H.; Ahmad M.R.; Takayanagi Y.; Edris M.Z.B.; Shamsul Baharin S.A.; Morimoto T.; Kawasaki Z.-I.; Baharuddin M.Z.; Cooray V. (Elsevier Ltd, 2025)
This study investigates the occurrence of chaotic pulse trains (CPTs) and regular pulse trains (RPTs) in tropical positive cloud-to-ground (CG) lightning flashes. These flashes are categorized into four types based on the initial polarity of the initial breakdown (IB) pulses and their relationship to the first return stroke (RS). A total of 71 positive CG flashes from five thunderstorm events were analyzed. The analysis reveals instances of CPTs and RPTs both before and after the first positive RS, along with the occurrence of mixed polarities in RPTs. Variations in IB pulse polarities and the presence of CPTs and RPTs before the first positive RS were observed, contrasting with previous findings in negative CG flashes. All positive CG flashes have been detected when cloud top height occurrences were between 12 and 18 km. In contrast, for negative CG flashes with CPTs and RPTs the cloud top height occurrences were between 5 and 12 km. It is interesting that CPTs and RPTs can be detected during IB process of positive CG flashes at relatively high altitude in the thundercloud. Perhaps due to low pressure at higher altitudes in the cloud, electrical process associated with CPTs and RPTs are easily discharged before the occurrence first positive return stroke. The altitudes of cloud top heights for the inverse polarity of IB pulses were located between 16 and 18 km. This research enhances the understanding of positive CG lightning initiation process and their relationship with CPTs and RPTs, as well as the occurrence of recoil leaders. ? 2024 Elsevier Ltd